Social Transformation Of The Indigenous Community Kasepuhan Sinar Resmi Sukabumi West Java - Kantirina Rachaju (Institute of Computer Science (IOCS), 2021)
Humans as social beings cannot live alone, they will need each other in socializing with each other. The importance of other humans in a community (society) will help achieve the desired goal, namely the development of potential and interaction between fellow humans. In line with that, the formation of a community will give birth to rules, values, social norms, culture within the community as a way of life that must be obeyed together. Changes and growth in the increasingly massive scope of society can affect changes in social life. Various aspects of course also change, such as: social, economic, cultural, cultural and technological aspects. This has contributed to a shift in the pattern of social interaction in social life. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that, the unit of the Kasepuhan Banten Kidul Indigenous Community in Sukabumi is known as the Kasepuhan Community / residents who carry out socio-cultural daily activities based on tatali paranti karuhun (traditions inherited from their ancestors). . The Kasepuhan community is an open society, they do not close themselves off from modern cultural life patterns as long as they do not conflict with the tatali paranti karuhun as their cultural basis, the incessant global culture and modernization do not make the people of the Kasepuhan Indigenous Unity of Banten Kidul become marginalized and isolated, or vice versa, their socio-cultural values ??have changed, individualism, materialistic, but they have so far been able to harmoniously combine state regulations, religion and tatali paranti karuhun in preserving their local wisdom as the implementation of the philosophy of life